Conclusions of a meeting of the Cabinet held in the Prime Minister's Room, House of Commons, S.W.1, on Friday, 27th February, 1959, at 11-15 a.m - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1959)
Relating to the federation of Nyasaland and Rhodesia, and the Prime Minister's visit to Moscow